Vertical Integration and Outsourcing Decision Impact On Firm Performance: A Review Based Research on the Influence of Organizational Governance On firm Performance. - Sikandar Shah; Dr. Wisal Ahmad; Dr. Muhammad Faizan Malik; Shah Raza Khan (Journal of Business & Tourism, 2021)
This studyexamines that how companies take decision of outsourcing and vertical integration a value-chain activity currently the most complex problem faced by most the organization around the globe and also find the relationship and highlight the role of every activity related to outsourcing and vertical integration. In result of survey and interviews of different small, medium and corporate level companies in KPK, procurement managers and operations managers mostly in view of that outsourcing is thebest way to work in the market, because of the cost reduction, minimumturnaround time and especially in the uncertain market of KPK.